Psychedelic Assisted Psychotherapy preparing your target using psychohistoriography: a Jamaican perspective - De La Haye, Winston; Walcott, Geoffrey; Eaton, Jordan; Beckford, Jhoelle; Greene, Janelle (Frontiers in Psychiatry, 2023)
The efficacy of psilocybin and other psychedelics as modes of treatment have been demonstrated through clinical trials and other studies in the management of a number of mental illnesses, including some treatment resistant cases. In Psychedelic Assisted Psychotherapy (PAP), psychedelics catalyze or enhance the experience fostered by psychotherapeutic methods. Psychohistoriographic Brief Psychotherapy, conceptualized by the late Professor Frederick Hickling in the 1970′s in Kingston, Jamaica, offers a pathway for exploration in the Jamaican context. Applied to individuals, Psychohistoriographic Brief Therapy (PBT) has already shown success in patients with personality disorders in Jamaica through a process which includes documenting life experiences in a psychohistoriogram. In the De La Haye psilocybin Treatment Protocol (DPTP), micro-doses of crushed, dried psilocybin mushrooms are taken throughout an 8-week outpatient process of documenting the components of the psychohistoriogram, making use of the increased openness and empathy associated with the use of psychedelic agents. These sessions are followed by supervised in-office therapeutic/mystical doses of crushed, dried psilocybin mushrooms in the 9th week. Given the legal status and availability of psilocybin containing products in a few countries like Jamaica, there is a potential role for a regulated psychedelic industry contributing to the body of useful and rigorous clinical research which is needed in this area. Clients could benefit as we venture into this new frontier in psychiatry.